Unveiling the potentials of Lawsonia inermis L.: its antioxidant, antimicrobial, and anticancer potentials - Joyroy,Nantikan; Ngiwsara,Lukana; Wannachat,Siriporn; Mingma,Ratchanee; Svasti,Jisnuson; Wongchawalit,Jintanart (PeerJ, 2025)
Background Lawsonia inermis L., commonly known as henna, is a traditional medicinal Indian plant used for anti-dandruff and antifungal purposes. The plant is rich in phytochemicals and is believed to have significant bioactivity potential. However, limited information is available on the phytochemical compositions of L. inermis cultivars in Thailand. Therefore, this study aims to assess the phytochemical constituents and investigate the bioactivity of L. inermis extract. Methods L. inermis leaf extracts were prepared by macerating in ethanol (HenE), methanol (HenM), chloroform (HenC), hexane (HenH), and water boiling (HenW). The phenolic and flavonoid contents were determined by Folin-Ciocalteu and aluminum chloride colorimetric methods. High-performance liquid chromatography (HPLC) was performed to qualify polyphenolic contents. Antioxidant activities were evaluated by using 2,2-Diphenyl-1-picrylhydrazyl (DPPH), 2,2′-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), and ferric reducing antioxidant power (FRAP) methods. Moreover, antibacterial activity was tested against two gram-positive and four gram-negative bacteria by the agar well diffusion and the broth dilution methods, and antifungal activity was carried out using the poisoned food technique. Additionally, the cytotoxicity of the extracts against MDA-MB-231, SW480, A549 and A549RT-eto cancer cell lines was determined by using (3-(4, 5-dimethylthiazolyl-2)-2, 5-diphenyltetrazolium bromide) (MTT) assay. The scratch wound healing assay was performed to determine the effect of anti-migration on A549 cells. Results Quantitative analysis revealed that HenE and HenM extracts had high phenolic and flavonoid contents. Gallic acid, catechin, ellagic acid, apigetrin, lawsone and quercetin were identified by HPLC. The HenE and HenM extracts exhibited strong antioxidant properties, and the extracts showed different inhibition growth against bacteria tested, especially B. cereus and S. aureus. In addition, all extracts had potential inhibitory activity to all fungal strains, especially HenE and Hen M, which exhibited strong antifungus activity against Penicillium sp. All extracts showed cytotoxic effects in the cell lines MDA-MB-231, SW480, A549 and A549RT-eto, except HenH. The HenE and HenM exhibited the best IC50 values of 57.33 ± 5.56 µg/ml and 65.00 ± 7.07 µg/ml against SW480 cells, respectively. The HenC, HenW, and HenH were found to suppress A549 cells migration. Discussion and Conclusion This study revealed that the L. inermis extracts, particularly those obtained from polar solvents (HenE and HenM), had a strong potency for antioxidant, antibacterial, and anticancer properties. Our findings highlight the valuable biological properties of extracts that can be promoted through additional investigation into their applications in Thailand for medicinal and industrial purposes.
Keywords: Lawsonia inermis; Phytochemicals; Antimicrobial activity; Antioxidant activity; Cytotoxicity; Anti-migration ability